Morphological changes in the offshore islands of Meghna estuary: Analysis of the erosion and accretion dynamics - Fariha Khatun; Ovi Ranjan Saha; Naila Matin (HydroResearch)
This study examines the morphological changes of ten offshore islands in the Meghna estuary of Bangladesh over thirty years, from 1989 to 2019, utilizing remote sensing and Geographic Information System (GIS) techniques. The study area, characterized by ever-changing hydrodynamic conditions due to the substantial discharge from the Ganges, Jamuna, and Meghna rivers, experiences significant sediment deposition and erosion. Our findings highlight a complex interplay between erosion and accretion processes across the estuary. Despite 1100 km2 of land being eroded, accretion processes were slightly more predominant, totaling 1210 km2, resulting in a net increase of 110 km2 in land area. Notably, islands like Swarna Dwip and Moulovi Char exhibited substantial land gains, while Manpura and the eastern part of Bhola experienced significant reductions, underlining the urgent need for targeted erosion mitigation strategies. The study also identifies significant sediment deposition near tidal confluence zones around Sandwip, Jahazer Char, and Urir Char, suggesting that these are key areas for conservation efforts. The research contributes valuable insights into the geomorphological dynamics within the Meghna estuary. It offers foundational knowledge for informed coastal management and sustainable development planning in one of the world's most dynamically evolving coastal environments.